english: english - Joko Sriwidodo (Unram Law Review, 2023)
Problems in Human Rights Court in enforcing the laws with human rights violations and gross human rights violations, the Human Rights Court has been established in the general judicial environment. Gross violations of human rights cases that recently occurred where unscrupulous members of the National Police committed acts of obstruction of justice in the case of the premeditated murder of Brigadier General Josua Hutabarat. Human rights violations by unscrupulous police officers in carrying out their duties as law enforcers may occur and must be enforced. The purpose of this study is to determine the gross violations of human rights and obstruction of justice by members of the National Police in the Hutabarat premeditated murder case. The research method used was a normative juridical approach, with the type of data used secondary data sourced from primary legal materials, such as the Criminal Code, the Corruption Eradication Law, and secondary legal materials. The result of this study shows that in the recent case of premeditated murder between members of the police, there are human rights violations by the National Human Rights Commission in the form of obstruction of justice. Related to the act of preventing, obstructing, and thwarting must be done intentionally. Analytically, the acts of” preventing” and “thwarting” can be categorized as deliberate, with the intention that the perpetrator wants the prohibited consequences to occur in the form of non-implementation of prosecution against the perpetrators of criminal acts.